A A STUDY ON THE PREVALENCE OF OVERWEIGHT AND OBESITY AMONG WOMEN AGED 20 YEARS AND ABOVE IN RURAL FIELD PRACTICE AREA OF SIMS, HAPUR - R K SEHGAL; GHOSHAL, VISHWANATH; UJJWAL SOURAV (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of the study was to assess the prevalence of overweight as well as obesity among women aged 20 years and above in a rural covered area of SIMS, Hapur, and to assess the risk factors for overweight and obesity in the above study population. Methods: This research was carried out in the rural field practice area of SIMS, Hapur, spanning from July 2022 to July 2023. The study focused on women aged 20 years and older who were residents of the SIMS field practice area. The following criteria were used to select the study participants: Women who were pregnant at the time of the study, those who could not be reached after two home visits, individuals taking chronic medications that might lead to weight gain, and those who were uncooperative were excluded from the study. Results: Out of the 500 participants in the study, 18.6% were categorized as underweight, 53.6% fell within the normal weight range, and 27.8% were considered overweight. Within the group of overweight individuals, a substantial 70.5% were classified as obese. The study revealed that the overall prevalence of overweight (defined as BMI>23) was 27.7%, while the prevalence of obesity (defined as BMI>25) stood at 19.8%. Furthermore, 29.9% of the women had a waist circumference exceeding 80 cm. Conclusion: Based on the findings from our current research, it can be deduced that women with higher levels of education and socioeconomic status, a family history of excess weight, a higher number of pregnancies, a lack of physical activity, insufficient sleep, and poor dietary choices are more likely to be at risk of becoming overweight or obese. To prevent the rising prevalence of excess fat and obesity, it is imperative to implement lifestyle and dietary modifications.